(3GdJhajb hGdhSGWI ai efGRYGJ GdYed GdLeGYjI (B: s (3OQGSI ebGQfI (B/ s - (3fGgO MSf MSjf Ydi YTQjs; (3GMeO MSf GdHQYj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3JYJHQ OQGSGJ GdLOhi GdGbJUGOjI ddeTQhYGJ ef GdehVhYGJ GdMjhjI GdJi MXjJ HGgJeGe cHjQ Ydi GdeSJhjjf GdfXQi hGdYedi ai GdOhd GdeJbOeI hGdfGejI (B: (3hEf cGfJ gPg GdGgejI GcKQ HUaI YGeI ai GdOhd GdfGejI HSHH eG JYGfjg gPg GdOhd ef fOQI fSHjI ai ehGQOgG GdGbJUGOjI eY YOe GdGSJNOGe GdGeKd dgPg GdehGQO (B: (3hHGdJGdi aEf gPg GdOQGSGJ JSGge ai YedjI GdJNUjU GdGeKd ddehGQO GdGbJUGOjI ShGA Ydi eSJhi GdhMOI GdGbJUGOjI Gh Ydi GdeSJhi Gdbhejs
(3jTJed Ydi edGMb(B: (3UaMGJ (B179-197s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2004s
(3HHdjhLQGajG(B: (3UaMGJ (B198-210s
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdehGQO GdGbJUGOjIs; (3OQGSGJ GdLOhi GdGbJUGOjIs; (3efGRYGJ GdYed GdLeGYjIs; (3GdJhajb s; (3GdhSGWI s; (3GdeaGhVI GdLeGYjIs; (3GdSdGe GdGLJeGYjs; (3GdefTCIs; (3GJaGbjGJ GdYed GdLeGYjIs; (3hSGFd aV efGRYGJ GdYed GdLeGYjIs; (3JShjI efGRYGJ GdYed GdLeGYjIs; (3GdfXGe GdbGfhfj ddhSGWI s; (3fabGJ GdhSGWI s; (3hSjW GdfRGY s; (3eSJhjGJ GdYed GdOhdjIs; (3eSJhjGJ GdYed GdYQHjI s; (3ELQGAGJ JMQjc GdhSGWI s; (3MGdGJ GdhSGWIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs